IMPACT OF MENTORSHIP ON ENTREPRENEURIAL SUCCESS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2026)
This study examined the impact of mentorship on entrepreneurial success in Anambra State, Nigeria. Three objectives and three corresponding research questions guided the study. The study adopted a descriptive survey of research design. The area of the study is Ogidi building material market Onitsha in Anambra State, while the population of study comprised of 450 respondents. Stratified random sampling technique was used to select the respondents for the study, hence 75 entrepreneurs’ business owners and 75 apprentices. The instrument for data collection was a structured questionnaire titled: Impact of Mentorship on Entrepreneurial Success (IMOES). The respondents used 4 rating scales such as 4= very High Extent (VHE), 3= High Extent (HE), 2= Low Extent (LE) and 1= Very Low Extent (VLE) to respond to the questionnaire, the instrument was validated by three experts, two from Business Education Department while one from entrepreneurship center. The reliability of the instrument was ascertained through its administration to twenty entrepreneurs in Enugu State and the test was repeated on the same group after two weeks interval, The Cronbach Alpha yielded a coefficient of 0.81, 0.77 and 0.75 for the three research questions in the clusters, respectively. Mean and standard deviation were used to analyze the data collected, any mean value of 2.50 and above was interpreted as high extent and any one below 2.50 was interpreted as low extent. The findings of the study among others revealed that mentorship motivates mentees for entrepreneurial success in Anambra State to a high extent. The study concluded that mentorship plays a critical and transformative role in fostering entrepreneurial development among individuals and recommended that Ministry of youth and development and other agencies should establish structured mentorship programs.
Keywords: Mentorship; Entrepreneurial Success